Post partum hemorrhage - Cabrera Ramos, Santiago (2015)
Post partum hemorrhage constitutes the main cause of maternal death in poor countries. The absolute risk of death by post partum hemorrhage is much less in wealthy countries than in poor countries. We review the causes of uterine atony –main cause of post partum hemorrhageand clinical and surgical procedures to treat this frightful complication.